Partnership in Leadership: Why and How Do Leading Powers Extend Managerial Privileges to Junior Partners?. (27th May 2021) - Heimann, Gadi; Paikowsky, Deganit; Kedem, Nadav
Abstract: This article seeks to explain states' success, either full or partial, in obtaining a place in an exclusive managerial forum and the managerial privileges this entails. We argue that the ability to join an exclusive forum and gain these privileges depends on three factors: the extent to which the potential junior partners' assets seem attractive to the forum's leaders; the extent of potential junior partners' solidarity with the leading powers; and the leading powers' ability to obtain legitimacy for including new members from the other states subject to the authority of the forum. These arguments are demonstrated through an examination of two test cases: the United Kingdom's partial success in achieving integration at the end of the 1940s by gaining informal privileges from the United States, and France's failure to gain institutionalized integration a decade later and its refusal to be satisfied with informal privileges.